Impact of Low-Dose Ketamine on the Usage of Continuous Opioid Infusion for the Treatment of Pain in Adult Mechanically Ventilated Patients in Surgical Intensive Care Units. (August 2019) - Buchheit, Jessica L.; Yeh, Daniel Dante; Eikermann, Matthias; Lin, Hsin
Background: Ketamine at subanesthetic doses has been shown to provide analgesic effects without causing respiratory depression and may be a viable option in mechanically ventilated patients to assist with extubation. The aim of this study was to evaluate the effects of low-dose ketamine on opioid consumption in mechanically ventilated adult surgical intensive care unit (ICU) patients. Methods: A retrospective review of mechanically ventilated adult patients receiving low-dose ketamine continuous infusion (1-5 µcg/kg/min) for adjunctive pain control admitted to surgical ICUs was conducted. Patients were included if they met an ICU safety screen for a spontaneous breathing trial (SBT) implying extubation readiness pending SBT results. The primary end point was the slope of change in morphine equivalents (MEs) 12 hours pre- and postketamine infusion. We hypothesized that low-dose ketamine would increase the slope of opioid dose reduction. Results: Forty patients were analyzed. The median dose of ketamine was 5 µg/kg/min (interquartile range [IQR]: 3.5-5) and the treatment duration was 1.89 days (IQR: 0.96-3.06). Prior to ketamine, the majority of patients received volume-controlled or pressure-supported ventilation with a median duration of 2.05 days (IQR: 1.38-3.61). The median time from the initiation of ketamine to extubation was 1.44 days (IQR: 0.58-2.66). For the primary outcome, there was a significant difference in the slope of ME changes from 1 to −0.265 mg/h 12 hours pre- and postketamine initiation ( P < .001). For the secondary outcomes, ketamine was associated with a decrease in vasopressor requirements (phenylephrine equivalent 70 vs 40 mg/h; P = .019). Conclusion: Low-dose continuous infusion ketamine in mechanically ventilated adult patients was associated with a significant increase in the rate of opioid dose reduction without adverse effects on hemodynamic stability.